Rationalizability and Correlated Equilibria - Brandenburger, Adam; Dekel, Eddie (Econometrica, 1987)
The authors discuss the unity between the two standard approaches to noncooperative solution concepts for games. The decision-theoretic approach starts from the assumption that the rationality of the players is common knowledge. This leads to the notion of correlated rationalizability. It is shown that correlated rationalizability is e quivalent to a posteriori equilibrium-a refinement of subjective corr elated equilibrium. Hence a decision-theoretic justification for the equilibrium approach to game theory is provided. An analogous equival ence result is proved between independent rationalizability, which is the appropriate concept if each player believes that the others act independently, and conditionally independent a posteriori equilibrium. Copyright 1987 by The Econometric Society.